Analysis of the opinions of early childhood education students on body language and expression - Gámez-Calvo, Luisa; Hernández-Beltrán, Víctor; Correia de Campos, Luis Felipe Castelli; M. Gamonales, José (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
Body language and expression is a fundamental tool for working on emotions and non-verbal communication. Therefore, the aim of the present study was to analyse the opinions on body expression of students of the Early Childhood Education teacher training degree in Extremadura (Spain). The sample was formed by eighty-four last-year students. The results show that the students do not consider that they have received the necessary training to use the contents related to body expression in their classrooms. In addition, the respondents consider that the educational centres do not give sufficient importance to body expression, as a result of the lack of material, lack of conditioning of the educational facilities and lack of time in the pupils' daily workdays. Therefore, the number of training credits in the field of body expression should be improved and increased, as well as the continuous and specific training of active education professionals.